Penentuan Aktivitas Antioksidan dan Antidiabetes Ekstrak Daun Matoa (Pometia pinnata J.R. Forst. & G. Forst.) secara In Vitro - Wulandari, Lestyo; Nugraha, Ari Satya; Himmah, Ulfa Aliyatul (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
Matoa (Pometia pinnata J.R. Forst. & G. Forst.) Matoa (Pometia pinnata J.R. Forst. & G. Forst.) is one of the plants that is used as a traditional medicine for diabetes mellitus due to an imbalance between the amount of ROS and antioxidants in the body. Therefore, it was carried out in vitro to see the antioxidant and antidiabetic activity in matoa leaf extract. The extraction of matoa leaves was carried out using the ultrasonication method for 30 minutes with methanol, ethanol, and ethyl acetate as solvents. Antioxidant activity is release through DPPH free radical inhibition, through the antidiabetic potential released by inhibiting the work of the α-amylase enzyme. Phytochemical test results showed the presence of secondary metabolites in the form of flavonoids, polyphenols, tannins, alkaloids, and terpenoids. The results of the research on methanol, ethanol, and ethyl acetate extracts of matoa leaves showed high antioxidant activity with IC50 values of 6.416 ± 0.176 ppm, 8.622 ± 0.066 ppm, and 170.637 ± 4.441 ppm, respectively, but they were less potent than vitamin C as a comparison which is 1.646 ± 0.015 ppm. Inhibition of the α-amylase enzyme showed IC50 values of 91.037 ± 0.750 ppm, 105,166 ± 2,423 ppm, and 785,436 ± 11,740 ppm in each of the methanol, ethanol, and ethyl acetate extracts while the IC50 value of acarbose as a comparison was 23,479 ± 0.347 ppm. The statistical data analysis of Pearson correlation showed that it had a positive relationship between the antioxidant and antidiabetic activity of matoa leaf extract as seen from the R-value of 0.998. The higher antioxidant activity, so the higher potential for inhibition of α-amylase enzyme.